Does time off work after injury vary by jurisdiction? A comparative study of eight Australian workers' compensation systems. Issue 5 (5th May 2016) - Collie, Alex; Lane, Tyler J; Hassani-Mahmooei, Behrooz; Thompson, Jason; McLeod, Chris
Abstract : Objectives: To determine whether the jurisdiction in which a work-related injury compensation claim is made is an independent predictor of duration of time off work following work injury, and if so, the magnitude of the effect. Setting: Eight Australian state and territory workers' compensation systems, providing coverage for more than 90% of the Australian labour force. Administrative claims data from these systems were provided by government regulatory authorities for the study. Participants: 95 976 Australian workers with workers' compensation claims accepted in 2010 and with at least 2 weeks of compensated time off work. Primary outcome measure: Duration of time lost from work in weeks, censored at 104 weeks. Results: After controlling for demographic, worker, injury and employer factors in a Cox regression model, significant differences in duration of time loss between state and territory of claim were observed. Compared with New South Wales, workers in Victoria, South Australia and Comcare had significantly longer durations of time off work and were more likely to be receiving income benefits at 104 weeks postinjury, while workers in Tasmania and Queensland had significantly shorter durations of time off work. Conclusions: The jurisdiction in which an injured worker makes a compensation claim has a significant and independent impact on duration of time loss. Further research is necessary to identify specific compensation system policies and practices that promote timely and appropriate return to work and reduce duration of time off work.